Fabrication of Multifunctional Nanofiber Mats by Emulsion Electrospinning of TPU/Fish Skin Gelatin Incorporating Plant Extract-Based Therapeutic Oil for Wound Dressing Applications - Keskinkaya, Ruya; Yildirim, Arzu; Caglayan, Seyma; Erdogan, Eray Sarper; Turker, Yurdanur; Dikmetas, Dilara Nur; Karbancioglu-Guler, Funda; Batirel, Saime; Guner, Fatma Seniha; Erol-Taygun, Melek (WILEY-V C H VERLAG GMBH, 2025)
In this study, for the first time thermoplastic polyurethane (TPU), fish skin gelatin (FSG), and H. perforatum oil (HPO) combine to form a new nanofiber material by using the emulsion electrospinning technique. Scanning electron microscope (SEM), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA) are used for the characterization studies. Moreover, antibacterial activities, in vitro wound healing and cytotoxicity of the TPU mats are also investigated. The SEM investigations reveal that the average diameters of defect-free TPU nanofiber mats with diverse HPO concentrations are approximate to 400-500 nm and suitable to mimic the native extracellular matrix (ECM) with these values. Moreover, although there is no antibacterial activity in the control TPU mat, the addition of the tannic acid crosslinker and 12% of HPO to the nanofiber mat acquires a 31.3% inhibition against Staphylococcus aureus and a 21.0% against Escherichia coli. Furthermore, the TPU nanofiber mat with the highest HPO concentration (12%) is non-toxic to the cells and tends to promote healing in vitro assay. Overall results indicate that the wound healing properties of the obtained HPO-encapsulated TPU nanofiber mats can be a promising candidate for wound dressing applications.
Keywords: emulsion electrospinning; fish skin gelatin (FSG); H. perforatum oil; thermoplastic polyurethane; wound dressing; IN-VITRO; CHITOSAN; NANOCOMPOSITE; POLYURETHANES; DEGRADATION; ADSORPTION; CHALLENGES; MEMBRANES; ACID; Materials Science; Polymer Science